A MULTIPLICIDADE DE LINGUAGENS - PEREIRA, BERENICE B. S.; PELISSON, GLADIS D. F. B.; LENZ, JARBAS D. A.; GOETTEMS, LISIANE; MACAGNAN, MARISTELA; BORGMANN, MARTA E.; SCHUWENGLER, NATÁLIA; RAMOS, NICOLE W.; MAGALHÃES, TIAGO V.; PEREIRA, BERENICE B. S.; et al. (Salão do Conhecimento, 2013)
Resumo